Peran Lutein dan Zeaxanthin dalam Formulasi AREDS 2: Mekanisme Protektif dan Implementasi Klinis pada Age-Related Macular Degeneration: Tinjauan Pustaka - Endy Juli Anto; Rusli, Kenvin (Cermin Dunia Kedokteran, 2026)
Lutein and zeaxanthin are carotenoids that serve as key components in the Age-Related Eye Disease Study 2 (AREDS 2) formulation, replacing beta-carotene from the original formulation due to safety concerns. These carotenoids exhibit dual protective mechanisms as blue light filters and antioxidants within the macula. This literature review aims to analyze the specific roles of lutein and zeaxanthin in AREDS 2, their molecular protective mechanisms, and their optimal clinical implementation in age-related macular degeneration (AMD). Literature searches were conducted through PubMed, Cochrane Library, and Google Scholar using the keywords "lutein", "zeaxanthin", "AREDS 2","macular pigment", and "photoprotection". Lutein and zeaxanthin selectively accumulate in the macula, forming macular pigment optical density (MPOD), which functions as blue light filter (400–500 nm) and free radical scavenger. Supplementation with lutein 10 mg and zeaxanthin 2 mg in AREDS 2 has been proven to increase MPOD and reduce the risk of age-related macular degeneration (AMD) progression by 10%–26%. Clinical implementation requires baseline MPOD evaluation, individualized response monitoring, and dose optimization based on nutritional status and patient-specific risk factors.